An ex-vivo human intestinal model to study Entamoeba histolytica pathogenesis. - Devendra Bansal; Patrick Ave; Sophie Kerneis; Pascal Frileux; Olivier Boché; Anne Catherine Baglin; Geneviève Dubost; Anne-Sophie Leguern; Marie-Christine Prevost; Rivka Bracha; David Mirelman; Nancy Guillén; et al. (Public Library of Science (PLoS), 2009)
Amoebiasis (a human intestinal infection affecting 50 million people every year) is caused by the protozoan parasite Entamoeba histolytica. To study the molecular mechanisms underlying human colon invasion by E. histolytica, we have set up an ex vivo human colon model to study the early steps in amoebiasis. Using scanning electron microscopy and histological analyses, we have established that E. histolytica caused the removal of the protective mucus coat during the first two hours of incubation, detached the enterocytes, and then penetrated into the lamina propria by following the crypts of Lieberkühn. Significant cell lysis (determined by the release of lactodehydrogenase) and inflammation (marked by the secretion of pro-inflammatory molecules such as interleukin 1 beta, interferon gamma, interleukin 6, interleukin 8 and tumour necrosis factor) were detected after four hours of incubation. Entamoeba dispar (a closely related non-pathogenic amoeba that also colonizes the human colon) was unable to invade colonic mucosa, lyse cells or induce an inflammatory response. We also examined the behaviour of trophozoites in which genes coding for known virulent factors (such as amoebapores, the Gal/GalNAc lectin and the cysteine protease 5 (CP-A5), which have major roles in cell death, adhesion (to target cells or mucus) and mucus degradation, respectively) were silenced, together with the corresponding tissue responses. Our data revealed that the signalling via the heavy chain Hgl2 or via the light chain Lgl1 of the Gal/GalNAc lectin is not essential to penetrate the human colonic mucosa. In addition, our study demonstrates that E. histolytica silenced for CP-A5 does not penetrate the colonic lamina propria and does not induce the host's pro-inflammatory cytokine secretion.